2016
DOI: 10.7554/elife.15598
|View full text |Cite
|
Sign up to set email alerts
|

Two-way communication between SecY and SecA suggests a Brownian ratchet mechanism for protein translocation

Abstract: The essential process of protein secretion is achieved by the ubiquitous Sec machinery. In prokaryotes, the drive for translocation comes from ATP hydrolysis by the cytosolic motor-protein SecA, in concert with the proton motive force (PMF). However, the mechanism through which ATP hydrolysis by SecA is coupled to directional movement through SecYEG is unclear. Here, we combine all-atom molecular dynamics (MD) simulations with single molecule FRET and biochemical assays. We show that ATP binding by SecA causes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
172
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(190 citation statements)
references
References 73 publications
(144 reference statements)
15
172
1
Order By: Relevance
“…In addition, protein translocation in this system appears to use both SecA-dependent pushing and Brownian motion-dependent sliding to achieve efficient transport (33). Since the mobility and role of the THF subdomain in protein transport remain controversial (39,40), additional studies will be required to resolve this matter. Further studies can now address the biochemical and structural requirements needed to transition from the preinitiation to postinitiation states.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, protein translocation in this system appears to use both SecA-dependent pushing and Brownian motion-dependent sliding to achieve efficient transport (33). Since the mobility and role of the THF subdomain in protein transport remain controversial (39,40), additional studies will be required to resolve this matter. Further studies can now address the biochemical and structural requirements needed to transition from the preinitiation to postinitiation states.…”
Section: Discussionmentioning
confidence: 99%
“…[98][99][100] Moreover, there is evidence that the bacterial Sec machinery employs and ATP-dependent Brownian ratchet mechanism for protein secretion. [101] Beyond bacterial secretion, the mechanism of translocation ratchet may be involved in import of bacteriophage DNA during the infection process. [102] In eukaryotic cells, precursor proteins are transported from the cytoplasm into mitochondria or the endoplasmatic reticulum.…”
Section: Brownian Ratchet Mechanisms Are Likely To Bias Macromoleculamentioning
confidence: 99%
“…[101] T4PS, type IV pilus system; T1SS, type I secretion system; T2SS, type II secretion system; T4SS, type IV secretion system. www.advancedsciencenews.com www.bioessays-journal.com hydrolysis and pmf whereas the later stages of translocation are powered by a translocation ratchet.…”
Section: Anthrax Toxin Translocase Secretion Of Anthrax Toxinmentioning
confidence: 99%
“…Two principal models have been proposed: (1) a processive power-stroke in which a fixed length of substrate is transported for each ATP molecule hydrolysed by SecA (Erlandson et al, 2008;Zimmer et al, 2008); and (2) a Brownian ratchet model in which passive diffusive motion is conferred directionality by gating at the expense of ATP hydrolysis (Allen et al, 2016;Liang et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies favour at least some element of diffusion: previously, we proposed a "pure" stochastic model, in which the free energy available from ATP binding and hydrolysis at SecA drives a Brownian ratchet at the SecY LG (Allen et al, 2016), while others have suggested a hybrid processive/stochastic model, in which ATP hydrolysis generates a power stroke ('push') on the polypeptide, but the latter is allowed to diffuse through the pore ('slide') (Bauer et al, 2014). This marks a shift from deterministic models based on static structural snapshots to a stochastic view in which intrinsic dynamics of the complex are taken into account (Corey et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%